2011
DOI: 10.4028/www.scientific.net/kem.470.123
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Strained Silicon by Electron Back Scattering Pattern Compared with Raman Measurement and Edge Force Model Calculation

Abstract: Global and local strained-Si samples, namely strained-Si on insulator (SSOI) wafer and a Si substrate with a patterned SiN film were each evaluated by electron backscattering pattern (EBSP). In the EBSP measurements for SSOI, biaxial tensile stresses (biaxial tensile strains and compressive strain perpendicular to the surface) were obtained, whose values were consistent with those obtained by UV-Raman spectroscopy. One-dimensional stress distributions in the Si substrate with the patterned SiN film were obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 14 publications
(13 reference statements)
1
8
0
Order By: Relevance
“…To precisely evaluate the edge stress relaxation by Raman spectroscopy, a resolution improvement technique, such as the super-resolution method, is necessary. 11,12) As a result, a consistent relationship between EBSP and Raman measurements, and FEM simulation was found in xx stress profiles. On the other hand, the results of EBSP measurement were not in agreement with those of FEM simulation and Raman measurement for the yy stress.…”
Section: Resultssupporting
confidence: 68%
See 2 more Smart Citations
“…To precisely evaluate the edge stress relaxation by Raman spectroscopy, a resolution improvement technique, such as the super-resolution method, is necessary. 11,12) As a result, a consistent relationship between EBSP and Raman measurements, and FEM simulation was found in xx stress profiles. On the other hand, the results of EBSP measurement were not in agreement with those of FEM simulation and Raman measurement for the yy stress.…”
Section: Resultssupporting
confidence: 68%
“…[6][7][8][9][10] We have reported that electron backscattering pattern (EBSP) measurement is useful for evaluating the stress tensor in Si nanostructures with high spatial resolution. [11][12][13][14][15][16] Raman spectroscopy is also useful for evaluating anisotropic biaxial stress with high stress sensitivity. 3,4,[11][12][13][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] In this study, we evaluated the anisotropic stress relaxation in mesa-shaped strained SiGe layers on Si substrates by EBSP measurement.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The superresolution method was applied to Raman spectroscopy (the so-called super-resolution Raman spectroscopy) to obtain extremely high spatial resolution. In super-resolution Raman spectroscopy, the bilateral total variation (BTV) deconvolution method was selected so that noise enhancement could be suppressed during the calculation [10][11][12][13][14]. In a previous study, it was reported that there was a good correlation between the stress calculated by the EFM and that measured by the Raman method with corrections for detection depth and beam spot size (in this case, the beam spot profile corresponded to the diffusion filter H) [15][16][17].…”
Section: Methods Of Stress/strainmentioning
confidence: 99%
“…A detailed explanation of the BTV method is given in [11]. The EFM with corrections for detection depth and beam spot size [10,11] was employed to check the validation and to estimate the spatial resolution before and after super resolution. In this model, it is assumed that the stresses are concentrated to film edge and the edge forces are dependent on film thickness and stress [18,19].…”
Section: Methods Of Stress/strainmentioning
confidence: 99%